2014
DOI: 10.14374/hfs.2014.22.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract from radix of Glycyrrhizae uralensis attenuate methamphetamine-induced hyperlocomotor activity

Abstract: Background and objective: Methamphetamine (Meth) is a widely abused psychostimulant that produces hyperlocomotion in rodents. Radix of Glycyrrhizae uralensis comprises a variety of bioactive components that have neuroprotective effects. In a previous study, we have demonstrated methanol extracts from radix of Glycyrrhizae uralensis (MEGR) suppress acute cocaine-induced extracellular dopamine release in the nucleus accumbens. In the present study, we investigated the effect of MEGR on acute Meth-induced hyperlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In the present study, the expression of repeated METH-induced locomotor sensitization was dose-dependently inhibited by MEGR (60 and 180 mg/kg/day), suggesting that MEGR exerts its preventative effects via blockade of the sensitizing pharmacological actions of METH. These data are compatible with previous studies showing that MEGR significantly inhibits acute cocaine-induced accumbal DA release via GABAb receptors [ 16 ] and acute METH-induced hyperlocomotion and accumbal DA synthesis [ 17 ], since the initial pharmacological effects of METH related to its rewarding properties are based on both the direct and indirect increases in accumbal DA. Additionally, the inhibitory effects of MEGR on the expression of METH-induced locomotor sensitization in the present study were blocked by the selective GABAb receptor antagonist SCH50911.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the expression of repeated METH-induced locomotor sensitization was dose-dependently inhibited by MEGR (60 and 180 mg/kg/day), suggesting that MEGR exerts its preventative effects via blockade of the sensitizing pharmacological actions of METH. These data are compatible with previous studies showing that MEGR significantly inhibits acute cocaine-induced accumbal DA release via GABAb receptors [ 16 ] and acute METH-induced hyperlocomotion and accumbal DA synthesis [ 17 ], since the initial pharmacological effects of METH related to its rewarding properties are based on both the direct and indirect increases in accumbal DA. Additionally, the inhibitory effects of MEGR on the expression of METH-induced locomotor sensitization in the present study were blocked by the selective GABAb receptor antagonist SCH50911.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies from our laboratory have demonstrated that MEGR and isoliquiritigenin suppress acute cocaine-induced accumbal DA release via GABAb receptors [ 16 ] and prevent acute METH-induced hyperlocomotion by inhibiting accumbal DA synthesis [ 17 ]. In the present study, we extended these findings, demonstrating that MEGR (60 or 180 mg/kg/day) dose-dependently inhibited repeated METH-induced locomotor sensitization, with nearly complete abolishment of sensitization induced by the 180 mg/kg dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty two rats were given subcutaneous (s.c.) administration of either saline or 0.4 mg/kg of (−)-nicotine hydrogen tartrate (Sigma, St. Louis, MO, USA) dissolved in saline (pH 7.2; all doses expressed as free base) twice a day for 7 consecutive days in their home cages, randomly assigned to drug-treated groups (3 groups, n = 7) and vehicle-treated groups (3 groups, n = 7), and then underwent 4 d of withdrawal [ 6 , 26 ]. During the withdrawal period, the rats were orally treated with either distilled water (DW) or MEGR (60 or 180 mg/kg/d, dissolved in DW) once a day for 4 d [ 20 , 21 ]. Immediately after the final dose of DW or MEGR, the rats were adapted to the locomotor testing boxes for 60 min and then systemically challenged with either nicotine (0.4 mg/kg) or saline [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, over the past decade, several studies have revealed G. radix has neuropharmacological properties such as neuroprotective, antidepressant, and anxiolytic effects [ 16 18 ]. In previous studies, we found extracts from G. radix suppressed acute cocaine- and methamphetamine- induced increases in accumbal DA levels [ 19 ] and prevented acute methamphetamine-induced hyperlocomotion in rats [ 20 ], indicating inhibitory effects of G. radix against pharmacological actions of psychostimulants. Moreover, in other studies, we also demonstrated G. radix improved the behavioral and neurochemical abnormalities caused by repeated psychostimulant treatment such that extracts from G. radix attenuated methamphetamine-induced locomotor sensitization and conditioned place preference [ 21 ] and isoliquiritigenin ameliorated repeated methamphetamine-induced loss of striatal dopamine transporter densities and tyrosine hydroxylase activities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%